Experimental characterizations of bimorph piezoelectric actuator for robotic assembly. (September 2017) - Ghosh, Bhaskar; Jain, Ravi K; Majumder, S; Roy, SS; Mukhopadhyay, Sumit
Piezoelectric actuator is one of the most versatile types of smart actuators, extensively used in different industrial applications like robotics, microelectromechanical systems, micro-assembly, biological cell handling, self-assembly, and optical component handling in photonics. By applying potential to a piezoelectric actuator, it can produce micro level deflection with large force generation, very fast response, and long-term actuation as compared to other actuators. The design and analysis of the bimorph piezoelectric cantilever using proportional–integral controller are carried out where the bimorph piezoelectric actuator is used as an active actuator for providing the dexterous behavior during robotic assembly. Characterization of bimorph piezoelectric actuator carried out by controlling voltage signal provides steady-state behavior which is verified by conducting experiments. A prototype of micro gripper is also developed which shows the potential of handling small lightweight objects for robotic assembly.